Cellular Metrology: Scoping for a Value Proposition in Extra- and Intracellular Measurements - Faruqui, Nilofar; Kummrow, Andreas; Fu, Boqiang; Divieto, Carla; Rojas, Fabiola; Kisulu, Florence; Cavalcante, Janaina J. V.; Wang, Jing; Campbell, Jonathan; Martins, Juliana L.; Choi, Jun-Hyuk; Sassi, Maria Paola; et al. (Frontiers in Bioengineering and Biotechnology, 2020)
the symptomatic irreproducibility of data in biomedicine and biotechnology prompts the need for higher order measurements of cells in their native and near-native environments. Such measurements may support the adoption of new technologies as well as the development of research programs across different sectors including healthcare and clinic, environmental control and national security. With an increasing demand for reliable cell-based products and services, cellular metrology is poised to help address current and emerging measurement challenges faced by end-users. However, metrological foundations in cell analysis remain sparse and significant advances are necessary to keep pace with the needs of modern medicine and industry. Herein we discuss a role of metrology in cell and cell-related R&D activities to underpin growing international measurement capabilities. Relevant measurands are outlined and the lack of reference methods and materials, particularly those based on functional cell responses in native environments, is highlighted. The status quo and current challenges in cellular measurements are discussed in the light of metrological traceability in cell analysis and applications (e.g. a functional cell count). An emphasis is made on the consistency of measurement results independent of the analytical platform used, high confidence in data quality versus quantity, scale of measurements and issues of building infrastructure for end-users.